Origins and Development of the Affirmative Policy in Malaya and Malaysia: A Historical Overview - Ariffin Omar (Kajian Malaysia, 2003)
It is often believed that the bumiputera policy is inextricably intertwined with the emergence of the United Malays National Organization OMNO)', a powerful Malay political party which have dominated the government since the inception of the Federation of Malaya and subsequently the Federation of Malaysia. While it is truc that the bumiputera policy flowered with thc New Economic Policy (NEP), the seeds of policies of safeguarding and favoring the natives had in-fact been sown during colonial times.